Coalition Dynamics in Transnational Social Movements: Analyzing the EU Food Policy Coalition. Issue 1 (2nd January 2023) - Shawki, Noha; Schnyder, Melissa
ABSTRACT: In the context of policy discussions surrounding the EU common agricultural policy in the period after 2020, civil society groups across Europe launched advocacy campaigns to transform the CAP and EU food systems. This article focuses on the EU Food Policy Coalition, a diverse coalition with a wide-ranging agenda. How did disparate civil society groups with different areas of focus that include the environment, public health, and global justice form a viable and cohesive advocacy coalition and develop a joint vision for a transformed food system? And how can this mostly Brussels-based coalition centred on a professional community engage grassroots and conscience communities in advocating for a more sustainable food system? We find that a diverse coalition can mobilise around a shared vision when a coalition broker brings diverse groups together, building on preexisting ties and trust and on the convergence of their ideologies. We also find that a diverse coalition engages different social movement communities, remains unified, and is effective when it is well-coordinated and organised as a segmentary, polycentric, and integrated network. This organisational structure allows for flexibility in participation and for dispersed leadership within the coalition, while keeping a unified focus around a set of key norms.